The Rise of Digital Business Models: Thriving in the Post-COVID Era - Malhotra, Rashmi; Malhotra, D.K. (Journal of Applied Business and Economics, 2023)
The COVID-19 pandemic has become an undeniable reality and has forced the world to seek out a “new normal” as we move forward into a post-pandemic era. In the face of this crisis, businesses are now confronted with the difficult task of adapting their business models to fit this new reality, which has been directly influenced by the pandemic. These challenges are the direct result of the pandemic, and this research aims to explore the key obstacles that businesses must overcome as they navigate the post-COVID-19 environment. Additionally, we will discuss several fundamental transformative methods that firms can adopt to not only survive, but thrive in this “new normal” and beyond. We will also examine the importance of technology and the digital transformation that companies must undergo in order to remain competitive in today's technology-driven world.